Compression tests on aluminum honeycomb and epoxy resin sandwich panels. Issue 2 (3rd July 2015) - Cheng, Shuliang; Zhao, Xuya; Xiao, Bo; Xin, Yajun
Abstract : In order to realize the functional integration and improve the bearing and energy absorption capability of aluminum honeycomb sandwich panel under compression, aluminum honeycomb and epoxy resin sandwich panels were made. By carrying out quasi-static compression experiments, we investigated their absorption function with different resin thickness, diameter of aperture, and thickness. The experiments indicated that the energy absorption function of the aluminum honeycomb sandwich panel declined with increase of resin thickness and length of aperture but improved with increase of specimen thickness.